Monitoring and moderating extreme indoor temperatures in low-income urban communities. (2nd February 2021) - Wilby, R L; Kasei, R; Gough, K V; Amankwaa, E F; Abarike, M; Anderson, N J; Codjoe, S N A; Griffiths, P; Kaba, C; Abdullah, K; Kayaga, S; Matthews, T; et al.
Abstract: Climate change presents significant threats to human health, especially for low-income urban communities in the Global South. Despite numerous studies of heat stress, surprisingly little is known about the temperatures actually encountered by people in their homes, or the benefits of affordable adaptations. This paper examines indoor air temperature measurements gathered from 47 living rooms within eight low-income communities of Accra and Tamale, Ghana. Using multiple temperature indices and a tiered analysis, we evaluate indoor temperature variations linked to roof type, ceiling insulation, presence of fans, and tree shade, for different housing types and locations. Our data reveal indoor temperatures in the range 22.4 °C to 45.9 °C for Accra, and 22.2 °C to 43.0 °C in Tamale. Using dummy regression analysis, we find that tree shade reduces the number of very hot days (>40 °C) and nights (>30 °C) by about 12 and 15 d per year, respectively. Building materials also strongly moderate indoor temperatures but in opposing ways: rooms with traditional mud walls and thatch roofs are on average 4.5 °C cooler than rooms in concrete block houses with uninsulated metal roofs during the day but are 1.5 °C warmer at night; rooms with ceiling insulation are on average 6.9 °C cooler in the day but 1.4 °C warmer at night. We conclude that sub-daily data are necessary for reporting extreme indoor temperatures, and that trade-offs between minimum and maximum temperatures require interventions to be assessed carefully before attempting to counter extreme heat inside homes.